Motivation on business management subjects in interdisciplinary degrees - Jimenez Jimenez, Maria del Amor (2024)
The implementation of interdisciplinary, joint or double degree study plans in university degrees is increasing, generating the need to analyze whether the subjects belonging to specific areas or disciplines can negatively affect the motivation of students with respect to the degree. For this reason, we consider it of great interest to reflect on the perception of this type of degree by students. We analyze the motivation of the students of the Degree in Cultural Management in front of the business branch subjects. The Learning and Motivation Strategies Questionnaire (CEAM II) has been used and statistical tests have been applied to study the behaviors of the different motivational dimensions and items, considering, in addition, the effect that the course variable can cause in the motivation of the students. The results reveal low levels of anxiety and an adequate adaptation of the students to the subjects related to business management of the degree. The importance attributed to the value of the task and the repercussions that this dimension has on other motivational subscales are relevant. This research is a necessary contribution to cover the empirical evidence in this field of research.